Nonisothermal curing kinetics of solid resole by differential scanning calorimetry - Pattarakamon Chaiwan (2019)
© 2019 Elsevier B.V. In this work, solid resoles with different formaldehyde (F) to phenol (P) molar ratios and various contents of hexamethylenetetramine (HMTA, accelerator) and sodium hydroxide (NaOH, catalyst) were designed and characterized. Curing behavior was investigated by differential scanning calorimetry to provide useful insights for applications. Curing kinetics were analyzed by the Vyazovkin isoconversional method. The results demonstrate that the activation energy of the higher F/P molar ratio systems is lower in the initial stage but higher in the latter stage. The activation energy of the higher HMTA and NaOH system is higher in the initial stage but lower in the latter stage. The thermal stability of cured resoles was evaluated by thermogravimetric analysis. The higher F/P molar ratios or higher contents of HMTA and NaOH provide better thermal stability. This is because these synthetic conditions give higher crosslinking densities. This makes them better potential candidates for heat-resistant materials.